Effect of variable-intensity running training and circuit training on selected physiological parameters of soccer players - Ambrozy, T.; Nowak, M.; Omorczyk, J.; Wrzesniewski, K.; Ozimek, M.; Duda, H.; Mucha, D.; Ceranowicz, P.; Palka, T.; Stanula, A.; Mucha, D. (Central European Journal of Sport Sciences and Medicine, 2018)
Proper planning of the training process based on individual LT and AT metabolic thresholds is essential to improve athletic performance. Development of endurance in soccer players is mainly based on continuous runs and variable-intensity runs, supplemented with strength conditioning and sport-specific training. The aim of the study was to analyse selected parameters of physical capacity of soccer players after 8-week variable-intensity running training and circuit training. The experiment was carried out in a group of 34 soccer players aged 21 to 26 years. The athletes were divided into two groups: 17 people in the experimental group and 17 people in the control group. The experimental group was involved in 30-minute tempo runs two times a week for 8 weeks with variable intensity at AT. In the same period, the control group performed two 60-minute continuous runs at the intensity of 70-75%HRmax. The determination of metabolic thresholds used two indirect tests: the multistage shuttle run test (beep test) and maximal lactate steady state test (MLSS) with author's own modification. In order to evaluate maximal heart rate (HRmax), the research procedure was started from the beep test (distance: 20 m). The speed at the first level was 8.5 km/h and increased with each level by 0.5 km/h. Training of the experimental group where variable exercise intensity was used caused a statistically significant increase in HRmax (by 1.9%) and blood lactate levels at the AT (by 20.5%). The training in the experimental group led to the statistically significant (p < 0.05) increase in the parameters of the following variables: HRmax (by 1.9%); lactate level (by 7.85); HR at the AT (by 1,9%); lactate level at the AT (by 20.5%). The assumptions of the experimental training did not cause statistically significant changes in pretest vs. posttest HRmax and blood lactate levels for the LT. Endurance training with high intensity is more effective in soccer players compared to training with moderate intensity. Development of special endurance in soccer should also assume the intensity and method of working similar to the method used during sport competition.